A patient-reported questionnaire for evaluating utilization of the National Essential Public Health Service Program in China among older adults with hypertension and diabetes - Liu, Lu; Liu, Meicen; Yang, Linghe; Chen, Xinyue; Liu, Yuanli; You, Lili (Frontiers in Public Health, 2025)
ObjectivesThis study aimed to develop a patient-reported questionnaire to assess service utilization and patient satisfaction among older adults with hypertension and diabetes in primary health-care centers operating under China’s National Essential Public Health Service Program (NEPHSP).MethodsThe questionnaire’s item pool was constructed on the basis of a logic model. A cross-sectional survey was conducted in three provinces of mainland China between November and December 2019. The questionnaire was evaluated using Cronbach’s alpha coefficients and confirmatory factor analysis (CFA) to refine items and assess internal consistency, construct validity, convergent validity, and discriminant validity.ResultsThe final questionnaire adopted a second-order factor model comprising three domains: essential services for all older adults, follow-up services for older adults with hypertension or diabetes, and patient satisfaction assessment. Through a two-step refinement process, nine factors encompassing 29 items were selected, including elements such as “health records and health education,” “blood pressure/glucose monitoring,” and “health education in follow-up.” Cronbach’s alpha coefficients indicated excellent reliability, with values of 0.899 and 0.906. The 29-item instrument had robust model fit for both hypertension and diabetes cohorts. The fit indices for the hypertension model included a Bollen–Stine bootstrap chi-square to degrees of freedom ratio (χ2/df) of 1.78, root mean square error of approximation (RMSEA) of 0.03, and goodness-of-fit index (GFI) of 0.97. Similarly, for the diabetes model, the fit indices were a Bollen–Stine bootstrap χ2/df ratio of 1.38, RMSEA of 0.02, and GFI of 0.97. CFA revealed factor loadings ranging from 0.516 to 0.940 for the hypertension model and from 0.504 to 0.943 for the diabetes model. All three first-order factors were significantly correlated with each other (p < 0.01), and their correlation coefficients were lower than the square root of the average variance extracted. The models demonstrated strong structural validity, convergent validity, and discriminant validity.ConclusionA valid and reliable questionnaire for evaluating service utilization and patient satisfaction among older adults with hypertension and diabetes in primary health-care center was developed in China. This instrument will serve as a practical tool for patient-reported assessments within the NEPHSP framework at primary health-care centers.